REVITALISASI WARISAN: PELATIHAN INOVATIF BATIK LUKIS KHAS MALANG UNTUK REGENERASI SENI DAN BUDAYA - Kurniawan, Bayu; Melyanawati, Adelliya; Santoso, Anang Setyo; Frisdyan, Anugrah Firmansyah; Zainuri, A’zunita; Alfina, Dinazat Gita; Zahroq, Erma Laelatul; Fauzi, Firman Arif Rian; Winarni, Fitri Ayu Sri; Dolu, Fitriyani (LPPM Universitas Bina Bangsa, 2024)
Batik art and culture is an important part of the embodiment of regional identity and unique culture. In the Malang area, painted batik is an artistic and cultural heritage that deserves to be protected and preserved. However, recently young people's interest and attention to the art of batik painting has decreased. For this reason, this community service activity aims to revitalize cultural heritage by conducting training in typical Malang batik painting as a regeneration of art and culture for students at SMPN 3 Lawang. The method used in this community service activity is descriptive qualitative. Data collection techniques include observation, documentation and surveys. Participants in this research were students at SMPN 3 Lawang. Data analysis was carried out by collecting data from observations and literature studies to obtain a conclusion. Based on research, community service activities in the form of painted batik training make students at SMPN 3 Lawang more knowledgeable about tools, materials, techniques, methods of making and various typical Malang batik motifs and have interest and skills in making typical Malang painted batik. So, it is hoped that Malang's typical painted batik can be preserved and cultivated by the younger generation as a regional artistic and cultural heritage